DEVELOPMENT OF AN EMAIL AND MULTI-USER CHAT SYSTEM (FULafia Journal of Science and Technology, 2020)
The electronic mail (Email) plays an unavoidable role in human communications. With the increasingly growing reliance on electronic mail there is an increasing demand to develop a cheap and readily available effective communication process amongst people in a closed group with similar interest. This research work considered the analysis and development of an electronic mail (Email) and a multiuser chat system to enhance effective communication. The analysis and implementation of Email and the multiuser chat system is subdivided into three stages namely: programing, database management, and networking. Using Java programming language; which involves the coding of the server and the client components, MySQL; which consist of the development of the database management system, and a wireless router; to provide internet connectivity, real time electronic messages, whether online or offline, can be sent and received at zero cost amongst a group of people who share the same area of communicative commonality.
Keywords: Database management; Java programming; MySQL